2021
DOI: 10.3389/fcell.2021.782841
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Chronic Angiotensin II Induces Selective Senescence of Kidney Endothelial Cells

Abstract: Angiotensin II can cause oxidative stress and increased blood pressure that result in long term cardiovascular pathologies. Here we evaluated the contribution of cellular senescence to the effect of chronic exposure to low dose angiotensin II in a model that mimics long term tissue damage. We utilized the INK-ATTAC (p16Ink4a–Apoptosis Through Targeted Activation of Caspase 8) transgenic mouse model that allows for conditional elimination of p16Ink4a -dependent senescent cells by administration of AP20187. Angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Most of the highly significant gene changes seen at 10 days in both groups did not persist after 14 days of holiday from palbociclib or after 14 days of continued AP after palbociclib + AP treatment, though many genes were dysregulated in the Residual Effect cohort with large-magnitude fold-change values, albeit to lesser degrees of statistical significance ( Figure 2 B). AP treatment alone produced few highly significant gene expression changes on the naïve mouse lung, which suggests that senescent cells are rare in naïve ATTAC mice of this age ( Supplemental Figure S2A ), as we also noted previously in other organs [ 43 ]. On the other hand, senescence-dependent gene expression induced after palbociclib treatment became apparent by concomitant administration of palbociclib + AP; comparison between the palbociclib-treated group and the combination-palbociclib + AP-treated group showed that addition of AP negated a large portion of the palbociclib-induced response ( Supplemental Figure S2B and Supplemental File S1 ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Most of the highly significant gene changes seen at 10 days in both groups did not persist after 14 days of holiday from palbociclib or after 14 days of continued AP after palbociclib + AP treatment, though many genes were dysregulated in the Residual Effect cohort with large-magnitude fold-change values, albeit to lesser degrees of statistical significance ( Figure 2 B). AP treatment alone produced few highly significant gene expression changes on the naïve mouse lung, which suggests that senescent cells are rare in naïve ATTAC mice of this age ( Supplemental Figure S2A ), as we also noted previously in other organs [ 43 ]. On the other hand, senescence-dependent gene expression induced after palbociclib treatment became apparent by concomitant administration of palbociclib + AP; comparison between the palbociclib-treated group and the combination-palbociclib + AP-treated group showed that addition of AP negated a large portion of the palbociclib-induced response ( Supplemental Figure S2B and Supplemental File S1 ).…”
Section: Resultssupporting
confidence: 82%
“…Additionally, in a different study from our lab using the p16-INK-ATTAC model, we observed endothelial senescence in kidneys after angiotensin II treatment of animals and its reversal after co-treatment with AP. This was paralleled by upregulation of both Cdkn1a and Cdkn2B in the kidneys, which was reversed by AP co-treatment [ 43 ]. It is noteworthy that these changes were confined to the kidneys, and no senescence signals were observed in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to high ambient glucose and TGFβ1 used in the present study, other mediators are also involved in DKD and may contribute to diabetes-associated cellular senescence in the kidney. Among these, vasoactive mediators like angiotensin II have been shown to induce senescence of renal endothelial cells 47 . In addition, microinflammation associated with hyperuricemia or uric acid per se may exert a pro-senescent and aging effect 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Senescence has also been shown to induce angiogenesis through the actions of SASP [21]. Our previous work also showed that angiotensin II was sufficient to induce senescence in kidney endothelial cells, and that selective clearance of 4 senescent cells reverses downstream effects of senescence and prevents senescence-mediated immune infiltration [49]. Senescent cells characterized by p16 INK4A expression accumulate during physiologic aging.…”
Section: Causes and Consequences Of Senescencementioning
confidence: 90%